2019
DOI: 10.4081/ijfs.2019.8107
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of knives used in a slaughterhouse by a commercial non-thermal UV-C treatment

Abstract: To assess the antimicrobial effect of a commercial UV-C system, knives inoculated with Escherichia coli and Staphylococcus aureus as well as naturally contaminated and collected from the wet and clean area of a slaughterhouse knives were examined. For inoculated knives, UVC treatment for 30 s reduced mean E. coli counts by 5.1 log CFU cm-2 and mean S. aureus counts by 4.5 log CFU cm-2. The presence of blood lowered mean reductions to 3.4 log CFU cm-2 for E. coli and to 2.5 log CFU cm-2 for S. aureus. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…It could be due to the fact that the distance of sharpener surface to the light source was less than the distance of other equipment and so UV dose received by sharpener surface was higher than other equipment. Raschle et al (2019) reported 0.6–0.8 log unit reductions in TAMB counts of knife samples used in commercial slaughterhouse after UV treatment for 30 s. In the present study, higher reduction value was obtained in TAMB counts of knife samples after UV treatment than Raschle et al (2019). Differences in log reductions may be due to using varying treatment times and UV source of varying efficiencies.…”
Section: Resultsmentioning
confidence: 41%
See 4 more Smart Citations
“…It could be due to the fact that the distance of sharpener surface to the light source was less than the distance of other equipment and so UV dose received by sharpener surface was higher than other equipment. Raschle et al (2019) reported 0.6–0.8 log unit reductions in TAMB counts of knife samples used in commercial slaughterhouse after UV treatment for 30 s. In the present study, higher reduction value was obtained in TAMB counts of knife samples after UV treatment than Raschle et al (2019). Differences in log reductions may be due to using varying treatment times and UV source of varying efficiencies.…”
Section: Resultsmentioning
confidence: 41%
“…E. coli was detected only in swab samples taken from the cut-proof glove before the treatment, but E. coli was completely inhibited after UV treatment ( P < 0.05). Similarly, in a study in which UV treatment was applied to knife samples obtained from a commercial slaughterhouse, a significant decrease was found in the number of E. coli after the treatment ( P < 0.05) (Raschle et al, 2019). Haughton et al (2011) reported that E. coli was totally inactivated on contaminated stainless steel surfaces in poultry processing plant by application of UV treatment similar to the results found in the current study.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations